Dialektika Komunikasi Multikultural: Studi Praktik Budaya Lokal dan Agama di Kampung Inggris Pare Kabupaten Kediri - Ellyda Retpitasari; Moh Turmudi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2026)
This study aims to determine the dynamics of multicultural communication, sociological and anthropological perspectives in Kampung Inggris Pare, Kediri Regency and to find out the process of local cultural and religious interpretation in Kampung Inggris Pare, Kediri Regency. The researcher uses qualitative type research with a phenomenological approach with a focus on the study of discussion issues, to what extent is it given to the study of multicultural communication dialectics in shaping local cultural and religious practices. The results of the study show that the role of cultural diversity in Kampung Inggris Pare greatly affects the dynamics of multicultural communication. Students and tutors from different cultural backgrounds must adapt their ways of communicating to achieve a common understanding and mutual benefit. This is influenced by the diversity of students, tutors and the local community. Viewed from a sociological and anthropological perspective, it is shown that multilultural communication in Kampung Inggris Pare includes an understanding of different cultural norms besides language. Despite the obstacles in multicultural communication, social adaptation and effective communication can be carried out in harmony. From the communication process between students, tutors, and the local community, cultural acculturation occurred considering that in Kampung Inggris Pare, immigrants came from various cultures and regions. The immigrant students and tutors come from various religions, many of them are influenced by the habits of the Muslim residents in Kampung Inggris Pare, especially about social ethics and manners. The influence of religion on communication and social interaction, namely religious traditions, also teach values indirectly, especially through the values taught by the local people in Kampung Inggris Pare.